2007
DOI: 10.1089/thy.2006.0293
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Esophageal Adenocarcinoma Presenting as a Thyroid Mass: Case Report and Review of the Literature

Abstract: Metastatic disease to the thyroid is not an unusual finding at autopsies, but it is rare to be found in clinical situations. We present the first case of adenocarcinoma of the proximal esophagus presenting as a thyroid mass in a young healthy patient without any previous history of malignancy. This case highlights the importance of thorough work-up when addressing a thyroid mass. A high index of suspicion should be maintained in order to be able to detect unusual etiologies of thyroid conditions, especially wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…Although the thyroid is a highly vascularized organ (being second after the adrenal gland), clinically significant metastases to the thyroid are uncommon [2,3,4]. Previously published studies on necrotic studies revealed that asymptomatic lesions are not unusual, as we assumed in the past, and they seem to occur more frequently than primary carcinomas of the gland [2, 5].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the thyroid is a highly vascularized organ (being second after the adrenal gland), clinically significant metastases to the thyroid are uncommon [2,3,4]. Previously published studies on necrotic studies revealed that asymptomatic lesions are not unusual, as we assumed in the past, and they seem to occur more frequently than primary carcinomas of the gland [2, 5].…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of metastatic disease to the thyroid ranged from 1.25 to 24% in previous studies [2, 3]. Although the thyroid is a highly vascularized organ (being second after the adrenal gland), clinically significant metastases to the thyroid are uncommon [2,3,4].…”
Section: Discussionmentioning
confidence: 99%
“…ITM originating from the gastro-esophagus is poorly documented. A review of the English-language literature, searching for patients with secondary cancerous growth in the thyroid formed by transmission of tumor cells from primary esophageal and gastric carcinoma disclosed a total of four [9-12] and five reported cases [7,13-16], respectively. This article presents an additional case of thyroid metastasis from esophageal carcinoma occurring in a Chinese man and reviews the related references.…”
Section: Discussionmentioning
confidence: 99%
“…The most common primary sites are the kidney, breast, and lung (see related references [3-6]). To the best of our knowledge there is little information to date in the English literature about thyroid metastasis from the esophagus, except for four published cases [9-12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation